Does the ileal brake mechanism contribute to sustained weight loss after bariatric surgery?. Issue 1 (8th June 2017) - Barreto, Savio G.; Soenen, Stijn; Chisholm, Jacob; Chapman, Ian; Kow, Lilian
Abstract : Bariatric surgery is currently the most effective strategy for treating morbid obesity. Weight regain following significant weight loss, however, remains a problem, with the outcome proportional to the period of follow‐up. This review revisits a well‐established physiological neurohormonally‐mediated feedback loop, the so called ileal brake mechanism, with a special emphasis on the gut hormone peptide tyrosine tyrosine. The manuscript not only highlights the potential role of the ileal brake mechanism in weight loss and weight maintenance thereafter following obesity surgery, it also provides a compelling argument for using this appetite suppressing feedback loop to enable sustained long‐term weight loss in patients undergoing surgery for morbid obesity.